2018
DOI: 10.3389/fpsyg.2018.02220
|View full text |Cite
|
Sign up to set email alerts
|

Introducing and Testing the Creepiness of Situation Scale (CRoSS)

Abstract: When people interact with novel technologies (e.g., robots, novel technological tools), the word “creepy” regularly pops up. We define creepy situations as eliciting uneasy feelings and involving ambiguity (e.g., on how the behave or how to judge the situation). A common metric for creepiness would help evaluating creepiness of situations and developing adequate interventions against creepiness. Following psychometrical guidelines, we developed the Creepiness of Situation Scale (CRoSS) across four studies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 69 publications
2
47
0
Order By: Relevance
“…On the one hand, this may indicate that Potosky's () aspect of transparency appears to be relatively low for automated high‐stake interviews. On the other hand, this is in line with former research that suggested that feelings of uncertainty and ambiguity are especially prevalent in novel situations where people do not know what to do, what to feel, or how to judge the situations (Langer & König, ; Tene & Polonetsky, ). This might also account for the result that the low‐stake interview was perceived as being less ambiguous, as it might be more familiar to use automation for low‐stake scenarios such as training or work scheduling (see also Lee, ; Zyda, ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…On the one hand, this may indicate that Potosky's () aspect of transparency appears to be relatively low for automated high‐stake interviews. On the other hand, this is in line with former research that suggested that feelings of uncertainty and ambiguity are especially prevalent in novel situations where people do not know what to do, what to feel, or how to judge the situations (Langer & König, ; Tene & Polonetsky, ). This might also account for the result that the low‐stake interview was perceived as being less ambiguous, as it might be more familiar to use automation for low‐stake scenarios such as training or work scheduling (see also Lee, ; Zyda, ).…”
Section: Discussionsupporting
confidence: 91%
“…One reason for this might be that people only observed the situation; thus they might not have experienced enough emotional immersion into the situation. This finding might also indicate that perceptions of the virtual character in the current study were not affected by potential negative emotional effects caused by the uncanny valley (Kätsyri et al, ; Langer & König, ; Mori, ; Mori et al, ).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations